A potential research target for cardiac rehabilitation: brain-derived neurotrophic factor - Zou, Jianpeng; Hao, Shijie (Frontiers in Cardiovascular Medicine, 2024)
Cardiovascular diseases pose a major threat to human life, functional activity, and quality of life.Patients with cardiovascular disease are always at risk for adverse cardiac events, decreased physical activity, psychoemotional disturbances, and limited social participation due to their varying pathologies. Therefore, personalized cardiac rehabilitation is of great significance in improving patients' physical and mental functions, controlling disease progression, and preventing deterioration. There is a consensus on the benefits of cardiac rehabilitation in improving patients' quality of life, enhancing functional activity, and reducing mortality. As an important part of cardiac rehabilitation， Exercise plays an irreplaceable role. Aerobic exercise, resistance training, flexibility training, and other forms of exercise are recommended by many experts. Improvements in exercise tolerance, lipid metabolism, cardiac function, and psychological aspects of the patients were evident with appropriate exercise interventions based on a comprehensive assessment. Further studies have found that brain-derived neurotrophic factor may be an important mediator of exercise's ability to improve cardiovascular health. Brain-derived neurotrophic factor exerts multiple biological effects on the cardiovascular system. This article provides another perspective on the cardiac effects of exercise and further looks at the prospects for the use of brain-derived neurotrophic factor in cardiac rehabilitation. Meanwhile, the new idea that brain-derived neurotrophic factor is a key mediator connecting the brain-cardiac axis is proposed in light of the current research progress, to provide new ideas for clinical rehabilitation and scientific research.